Music and Early Language Acquisition - Brandt, Anthony K.; Slevc, Robert; Gebrian, Molly (Frontiers in Psychology, 2012)
Language is typically viewed as fundamental to human intelligence. Music, while recognized as a human universal, is often treated as an ancillary ability—one dependent on or derivative of language. In contrast, we argue that it is more productive from a developmental perspective to describe spoken language as a special type of music. A review of existing studies presents a compelling case that musical hearing and ability is essential to language acquisition. In addition, the authors challenge the prevailing view that music cognition matures more slowly than language and is more difficult; instead, the authors present evidence that music learning matches the speed and effort of language acquisition. We conclude that music merits a central place in our understanding of human development.